A Project Report on Root Cause Analysis of Power Loss and Air Oil Exchanger Leak in TM333-2B2 Engine - KRISHNA REDDY S V, LOKESHA S, CHANDRANATH JAIN S S (2008)
INTENAL GUIDE: G AMARNATH, MVJCE EXTERNAL GUIDE: AMRUTH KUMAR, HAL
Keywords: Air Oil Exchanger Leak